Methods of macroeconomic dynamics - Turnovsky, Stephen J. (Cambridge, Mass. : MIT Press, 1995)
Methods of Macroeconomic Dynamics provides a comprehensive treatment of dynamic modeling for first- and second-year graduate students. It focuses on certain key macroeconomic models - selected from early as well as recent research - to teach students how dynamic modeling is used to analyze the effects of policy on economic growth and performance. Large portions of the text are devoted to rational expectations models and to the representative agent model in continuous time.
Professionals will find the book useful as a reference that offers both a broad overview of the evolution of methods of macroeconomic dynamics and a detailed explanation of the technical aspects of the most recent dynamic models.
I. Introduction and Overview. 1. Traditional Macrodynamics. 2. A Dynamic Portfolio Balance Macroeconomic Model -- II. Rational Expectations. 3. Rational Expectations: Some Basic Issues. 4. Rational Expectations and Policy Neutrality. 5. Nonuniqueness Issues in Rational Expectations Models. 6. Rational Expectations and Saddlepoint Behavior. 7. The Stability of Government Deficit Financing under Rational Expectations. 8. Macroeconomic Stabilization Policy under Rational Expectations -- III. Intertemporal Optimization. 9. The Representative Agent Model. 10. Equilibrium in a Decentralized Economy with Distortionary Taxes and Inflation. 11. A Dynamic Analysis of Taxes. 12. The Representative Agent Model in the International Economy. 13. An Introduction to Endogenous Growth Models -- IV. Continuous-Time Stochastic Models. 14. Continuous-Time Stochastic Optimization. 15. A Stochastic Intertemporal Model of a Small Open Economy.
Includes bibliographical references and index.
Keywords: Macroeconomics; Macroeconomics -- Mathematical models; Statics and dynamics (Social sciences)